Translesional Fractional Flow Reserve is Related to Plaque Components in Coronary Artery Disease: A Study Combining Pressure Wire and NIRS-IVUS Analysis - Jin, Uram; Choi, So Yeon; Jung, Jisung; Lee, Jungil; Mintz, Gary S.; Seo, Kyoung Woo; Yang, Hyoung Mo; Lim, Hong Seok; Choi, Byoung Joo; Yoon, Myeong Ho; Shin, Joon Han; Tahk, Seung Jea (Journal of Invasive Cardiology, 2021)
Objectives. It remains unclear whether atherosclerotic plaque structure or composition is related to translesional biomechanical stresses in coronary artery disease. The aim of this study was to evaluate the association between translesional pressure parameters (using a pressure wire) and plaque characteristics (using a combined near-infrared spectroscopy [NIRS] and intravascular ultrasound [IVUS] imaging catheter). Methods. Fractional flow reserve (FFR), delta (Δ) FFR, and Δ pressure were obtained during adenosine-induced maximum hyperemic status. Lipid core burden index (LCBI) and maximum LCBI within 2 mm (maxLCBI2mm) and tomographic anatomy were evaluated by NIRS-IVUS. Results. Sixty-six lesions from 57 patients were analyzed (57 lesions for FFR, 45 lesions for ΔFFR). There was a negative correlation between FFR and maxLCBI2mm (r=-0.264; P=.049) and a positive correlation between ΔFFR and maxLCBI2mm (r=0.299; P=.049). ΔFFR of lesions with maxLCBI2mm ≥500 was significantly higher than maxLCBI2mm <500 (0.159 ± 0.085 vs 0.104 ± 0.075, respectively; P=.04). By receiver-operating characteristic curve analysis, ΔFFR ≥0.1 was a predictor for maxLCBI2mm ≥500 (area under curve, 0.707; 95% confidence interval, 0.552-0.862; P=.03). On multivariate analysis, ΔFFR was the only predictor of maxLCBI2mm (β=0.347; P=.03). Conclusion. ΔFFR across a coronary artery lesion is related to lipid core burden assessed using NIRS-IVUS and might be a meaningful predictor of high-risk plaque (plaque with high lipid content).
Keywords: Coronary Angiography; Coronary Artery Disease; Coronary Vessels; Fractional Flow Reserve, Myocardial; Humans; Plaque, Atherosclerotic; Predictive Value of Tests; Ultrasonography, Interventional; coronary artery disease; fractional flow reserve; intravascular ultrasound; near-infrared spectroscopy; plaque composition